Impact of 10 sessions of whole body cryostimulation on cutaneous microcirculation measured by laser doppler flowmetry - Szygula, R.; Dybek, T.; Klimek, A.; Tubek, S. (Journal of Human Kinetics, 2011)
The aim of the present study was to evaluate the basic and evoked blood flow in the skin microcirculation of the hand, one day and ten days after a series of 10 whole body cryostimulation sessions, in healthy individuals. The study group included 32 volunteers - 16 women and 16 men. The volunteers underwent 10 sessions of cryotherapy in a cryogenic chamber. The variables were recorded before the series of 10 whole body cryostimulation sessions (first measurement), one day after the last session (second measurement) and ten days later (third measurement). Rest flow, post-occlusive hyperaemic reaction, reaction to temperature and arterio-venous reflex index were evaluated by laser Doppler flowmetry. The values recorded for rest flow, a post-occlusive hyperaemic reaction, a reaction to temperature and arterio - venous reflex index were significantly higher both in the second and third measurement compared to the initial one. Differences were recorded both in men and women. The values of frequency in the range of 0,01 Hz to 2 Hz (heart frequency dependent) were significantly lower after whole-body cryostimulation in both men and women. In the range of myogenic frequency significantly higher values were recorded in the second and third measurement compared to the first one. Recorded data suggest improved response of the cutaneous microcirculation to applied stimuli in both women and men. Positive effects of cryostimulation persist in the tested group for 10 consecutive days.